Exploring students’ perceptions of key service attributes in vocational education - Rasyidi, Muharar; Putra, Bayu Karunia; Azmi, M. Ulul; Wati, Kurnia; Ernawati, Novi (Asian Journal Collaboration of Social Environmental and Education, 2025)
Background: In an increasingly competitive educational landscape, understanding students’ perceptions of service attributes has become essential. Educational institutions are not only expected to deliver academic knowledge but also to provide high-quality services that meet students’ expectations. Methods: This research employed a descriptive approach using questionnaires for data collection. The sampling technique used was purposive sampling with a total of 82 student respondents. The study was conducted at one of the vocational schools in West Lombok. Data were analyzed using frequency distribution analysis. Findings: The findings show that although the majority of educational service attributes were rated as good (e.g., teacher adequacy 57.3%, laboratory equipment 50%, computer facilities 42.7%), toilet facilities (rated not good or very bad by 23.2% of students) and education costs (perceived as expensive or very expensive by 37.8%) received the lowest satisfaction scores, highlighting critical service gaps that vary by gender and require targeted design improvements. Conclusion: The analysis results show that most educational service attributes such as teacher competence, number of educators, syllabus availability, learning facilities, and school infrastructure are rated as good. However, two attributes, namely toilet facilities and education costs, were perceived as less satisfactory by students. Novelty/Originality of this article: This study provides empirical contributions by identifying the educational service attributes that most influence student perceptions at the vocational high school level. The focus on evaluating toilet facilities and the cost structure of education offers concrete directions for improving service quality management.